Clinical and Biochemical Characteristics of Pediatric Diabetic Ketoacidosis Admissions to COVID-19 Free UAE Tertiary Center during Pandemic - Shoroogh Marei; Dalia Ra’a Said; Raya Almazrouei; Walid Kaplan; Noura Al Hassani (Dubai Diabetes and Endocrinology Journal)
Background: COVID-19 pandemic led to delayed diagnosis and increase in number and severity of type 1 diabetes mellitus (T1DM) and diabetic ketoacidosis (DKA) cases in pediatric population worldwide. The indirect impact of the pandemic on pediatric DKA admissions to COVID-19-free hospitals worth to be evaluated. Objectives: Our aim was to evaluate the characteristics and severity of DKA admissions before and during the pandemic to COVID-19-free hospital. Methods: This descriptive retrospective study included 130 episodes of DKA for patients aged below 16 years admitted to Tawam Hospital, a COVID-19-free hospital, between March 2017 and Feb 2021. Data from March 2020 to Feb 2021 (pandemic) were compared to the previous 3 years, March 2017 to Feb 2020 (pre-pandemic). Data were retrieved from the electronic records and analyzed using STATA13. Results: We evaluated 130 DKA admissions (63 pandemic and 67 pre-pandemic). The majority of patients in the pandemic group were in, the age group of (6–11.9 years) (54% vs. 23.9%, p = 0.001), and higher proportion of them was diagnosed with new-onset diabetes (42.9% vs. 25.4%, p = 0.035). Overall, there was no significant difference in symptoms duration, DKA severity, or time to DKA resolution, but there was a difference in the median (IQR) HbA1C, 11% (9.4–12.95) vs. 10.15% (9.27–11.80) (p = 0.0297) in the pandemic and pre-pandemic groups, respectively. Conclusion: In our COVID-19-free hospital, the pandemic and service reallocation has led to an increased rate of DKA admissions with increased number of newly diagnosed T1DM. Clinical presentation and severity were not adversely affected.